Application of Modified Sliding Anastomosis in the Repair of Aortic Coarctation. (15th May 2020) - Chen, Wangping; Fan, Chengming; Tang, Shiyuan; Zhou, Wenwu; Iroegbu, Chukwuemeka Daniel; Li, Jiarong; Wu, Xiaoming; Yang, Jinfu
Abstract : Objectives . To evaluate the early and midterm results of a modified sliding anastomosis technique in patients with aortic coarctation. Materials and Methods . In this study, we reported a new repair method and compared the early and midterm outcome(s) with a conventional surgical approach for the management of patients with aortic coarctation. Forty-eight aortic coarctation patients with a narrowed segment length longer than 2 cm were operated at our department's pediatric surgical division. Excision of the coarctation and end-to-end anastomosis was carried out in twenty-five patients (control group). In contrast, a modified sliding technique was used for twenty-three cases in the observation group. Other accompanying cardiac anomalies simultaneously repaired included ventricular septal defect and patent ductus arteriosus. All patients received 1.5-10 years of postoperative echocardiographic follow-up. Results . This is a retrospective study carried out between January 2005 and June 2018. The study population consisted of forty-eight patients, which included twenty-six male and twenty-two female patients, with an average age of 5.2 ± 1.9 months (range, 28 days to 1 year). There was no mortality. The operative time, the number of intercostal artery disconnection, the drainage volume, and arm-leg systolic pressure gradient postoperation were less in the observation group as compared to the control group (p < 0.05 ). Also, cases with an anastomotic pressure gradient exceeding 10 mmHg during follow-up were less in the observation group as compared to the control group (p < 0.05 ). The postoperative complications encountered were chylothorax (control group 2 cases vs. observation group 0) and pulmonary atelectasis (control group 4 cases vs. observation group 1). They all, however, recovered after conservative treatment. Three patients in the control group underwent balloon angioplasty (reintervention) postoperative 2-4 years due to an increase in the anastomotic pressure gradient (>20 mmHg). After reintervention, the anastomotic pressure gradient reduced to 14 mmHg, 15 mmHg, and 17 mmHg, respectively. Conclusions . For long segment aortic coarctation patients (longer than 2 cm), the use of the modified sliding anastomotic technique effectively helps to retain more autologous tissues, enlarge the diameter of the anastomosis, and decrease anastomotic tension and vascular injury. Therefore, this technique provides a new idea for the surgical treatment of aortic coarctations.